Awareness and utilization of Swedish youth clinics among migrants enrolled in Swedish language programmes: a cross-sectional study - Amanda Lundberg; Anna-Karin Hurtig; Faustine Kyungu Nkulu-Kalengayi (Global Health Action)
Background Previous research has highlighted inequalities in access to Swedish youth clinics (YCs). These inequalities exist not only between non-migrant and young migrant populations but also within various migrant groups. Objectives To assess awareness and utilization of Swedish YCs among migrants enrolled in Swedish language programmes and explore associated factors. Methods This cross-sectional study involved 1,112 migrants aged 15−65. The analytical sample included 642 (57%) participants who answered the main outcome question about awareness of YCs. Descriptive statistics, bivariate, and multivariate log-binomial regression analyses using a Bayesian approach were applied to summarize the data and identify factors associated with awareness and utilization of YCs among migrants. Results The results revealed that 30% of all participants and 40% of the participants aged 15–25 years had heard of YCs. Additionally, 23% of the target group (15−25 years) had ever visited one. During descriptive and bivariate analyses, socio-demographic variations were evident in YCs’ awareness and utilization. However, in multivariate analyses, only the associations between awareness and year of arrival, and YCs’ utilization and year of arrival and type of residence permit, remained statistically significant. Conclusion This study highlights the level of awareness of YCs among migrants attending Swedish language programmes and their utilization by those aged 15−25 years, potentially impacting their access to crucial services and resources. Targeted interventions and sustainable strategies beyond one-time interventions are essential to address the specific needs of different socio-demographic groups and ensure equitable access to YCs’ information and services.